Humanist Relationships Between Police and Prisoners: A Cyberpragmatic Study - Wenny Wijayanti; Ardi Wina Saputra (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The background of this research is the existence of humanist relations between police and prisoners. This research aims to find humanist relations in the YouTube platform @indrasucipta. This type of research is qualitative research. The data source in this research is the @indrasucipta YouTube platform. The data analysis used in this research is cyberpragmatic analysis adapted from Fransisco Yus's cyberpragmatic theory. The results of the study prove that (1) the @indrasucipta youtube account is relevant to invite its audience to be moved in the action of spreading humanitarian values, (2) the @indrasucipta youtube account is responded to by its audience when taking the context of sharing with prisoners.